The relative impact of customer and technology orientations on innovation and export performance - Hortinha, Paula (2015)
Firms are constantly challenged by the trade-off between two types of strategic orientations: customer and technology. Yet, research directly addressing this topic is scarce and few recommendations exist on which orientation to emphasize. Using resource based view and organizational learning theory, this thesis addresses the relative impact of customer and technology orientations on export performance by considering the mediating role of innovation. Two innovation capabilities are considered: exploratory innovation – aimed at developing new product-market domains - and exploitative innovation – aimed at improving existing product-market positions. With the purpose of gaining more insights on those relationships, they are also examined under the influence of internal factors – past financial performance – and external factors – customer turbulence and technological turbulence. An exploratory study supported the survey instrument development. Data was collected through an on-line survey, resulting in a sample of 170 Portuguese exporters operating in technological manufacturing industries. We gathered data from two respondents within the each firm, the export manager and the R&D manager. Data analysis was conducted using Partial Least Squares, a variance-based structural equation modelling technique. Our results support the mediating role of exploratory and exploitative innovations. Moreover we have found that a customer orientation is as important as a technology orientation to the development of innovation capabilities. However, when past performance is low or the technological environment is highly turbulent, customer orientation plays a greater role. Implications of these findings for international marketing researchers and managers are presented and future research directions are provided.